"Now for a barrel roll" [Paul Keating and John Dawkins] - Pryor, Geoff, 1944- (1992)
Prime Minister Paul Keating is in no mood to waste time when the Government announces plans for Qantas to buy up Australian Airlines (the Government-owned domestic carrier), contrary to Labor policy, presenting the ALP Federal Executive with a fait accompli.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Part of the Pryor collection of cartoons and drawings.
Published in the Canberra Times on 3 June 1992.
Also available online
Keywords: Keating, Paul, -- 1944- -- Caricatures and cartoons; Dawkins, John, -- 1947- -- Caricatures and cartoons; Politicians -- Australia -- Caricatures and cartoons; Prime ministers -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1990-2001 -- Caricatures and cartoons; Federal politicians